Institutionalism - Peters, B. Guy.; Pierre, Jon.; Sage eBooks (Los Angeles, Calif. ; London : SAGE, 2007)
Institutional explanations are one of the most important means of understanding the choices made by governments and other actors in society. This work presents a collection of the key readings in institutional theory and its applications to political phenomena.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Political science -- Philosophy; Public institutions; Electronic books